2021
DOI: 10.1042/bsr20210977
|View full text |Cite
|
Sign up to set email alerts
|

In vivotherapeutic exploring forMori foliumextract against type 2 diabetes mellitus in rats

Abstract: Background: The study was aimed to investigate the potential therapeutic effect of Mori folium aqueous extracts (MFAE) on type 2 diabetes mellitus (T2DM) in vivo. Methods and Results: A rat model of T2DM was established with the combination of high sugar and high fat diet (HSFD) and streptozotocin (STZ). The T2DM rats were administrated with low (2 g kg-1) and high (5 g kg-1) dose of MFAE for 60 consecutive days. The biochemical indices of glucose metabolism disorders, insulin resistance and oxidative stress w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Fufang Fanshiliu decoction (FFSLD) is a traditional Chinese medicine formula composed of 10 different herbal medicines and has been used for diabetes therapy for more than seven years in clinics. Associated research studies showed that the drugs in FFSLD, for instance, Psidium guajava L. (Fanshiliuye) [ 12 ], Morus alba L. (Sangye) [ 13 ], Euonymus alatus (Thunb.) Sied.…”
Section: Introductionmentioning
confidence: 99%
“…Fufang Fanshiliu decoction (FFSLD) is a traditional Chinese medicine formula composed of 10 different herbal medicines and has been used for diabetes therapy for more than seven years in clinics. Associated research studies showed that the drugs in FFSLD, for instance, Psidium guajava L. (Fanshiliuye) [ 12 ], Morus alba L. (Sangye) [ 13 ], Euonymus alatus (Thunb.) Sied.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, our study has confirmed that diabetes mellitus can induce visual fatigue, lens opacity and transparency reduction, and increased hepatic MDA concentrations in rats. Additionally, it decreased hepatic GSH concentrations and SOD, CAT, GSH, GR, and GSH-Px activities [27,28]. When the watersoluble, purified lutein beverage was administered to rats, visual fatigue was attenuated.…”
Section: Discussionmentioning
confidence: 98%
“…Rosmarinic acid, caffeic acid, rutin, and quercetin form PV increased serum-insulin, attenuation of α-amylase and α-glucosidase ( Raafat et al, 2016 ). Aqueous extract of MA improved glucose metabolism disorders, ameliorated the antioxidative ability, and decreased insulin resistance via IRS-1/PI3K/Glut-4 signaling pathway ( Cai et al, 2016 ; Lyu et al, 2021 ). Both MA extract ( Wu et al, 2017 ) and CI water extract ( Nepali et al, 2018 ) exert anti-diabetic activity by regulating the AMPK pathway in diet-induced obesity mice models.…”
Section: Biological Activitiesmentioning
confidence: 99%